A cross-sectional study of bovine tuberculosis in selected dairy farms in Ethiopia - Ameni, G.; Bonnet, P.; Tibbo, Markos (2003)
A cross-sectional study to determine individual animal prevalence of bovine tuberculosis (BTB) was conducted on 1171 dairy cattle in 12 randomly selected dairy farms in Ethiopia between January 1999 and May 2001 using comparative intradermal tuberculin (CIT) test and bacteriologic study through milk culturing. An overall individual animal prevalence of 46.8% (548 of 1171 animals) and a herd prevalence of 91.7% (11 of 12 farms) were recorded in 12 dairy farms by the CIT test. There were significant (P <0.0001) differences in individual prevalence between farms and breeds (pure Holstein and their crosses with Zebu). There was positive correlation (r = 0.41) between herd size and prevalence of bovine tuberculosis. Furthermore, a negative linear association (R2 = 0.24) was found between mean score of management of the farm and prevalence, indicating that the prevalence of bovine tuberculosis could be improved by sanitary measures. Breed and management affected the prevalence of BTB (R2 = 0.30) as confounding variables. Mycobacterium bovis was isolated from the milk of 13.3% (4 of 30) reactor cows. The widespread occurrence of BTB in the study farms and isolation of M. bovis from the milk of reactor cows signify its economic importance and potential risk to public health. Generalization and improved use of milk pasteurization within all dairy subsectors is recommended, and this would affect the competitiveness of the dairy sector in Ethiopia.